2019
DOI: 10.3390/ani9080574
|View full text |Cite
|
Sign up to set email alerts
|

The Blood and Muscle Expression Pattern of the Equine TCAP Gene during the Race Track Training of Arabian Horses

Abstract: Horse musculature has been shaped through evolution by environmental and human factors, which has resulted in several extraordinary adaptations to physical effort. Skeletal muscle plasticity results from the response to mechanical stimulation causing hypertrophy, where sarcomeres increase the muscle’s cross-sectional area under the influence of contractile forces. The aim of the present study was the evaluation of transcript abundance of the telethonin (TCAP) gene, which is a part of the sarcomere macromolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Z-disc protein plays important roles in sarcomere assembly, stretch sensing, sarcomere-plasma membrane interactions, muscle development and functional regulation [30][31][32]. Studies have demonstrated that stretching exercise can induce the expression of TCAP and the transcriptional abundance increases with exercise intensity [29,33]. TCAP is mainly expressed in myocardial and skeletal muscle tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Z-disc protein plays important roles in sarcomere assembly, stretch sensing, sarcomere-plasma membrane interactions, muscle development and functional regulation [30][31][32]. Studies have demonstrated that stretching exercise can induce the expression of TCAP and the transcriptional abundance increases with exercise intensity [29,33]. TCAP is mainly expressed in myocardial and skeletal muscle tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that stretching exercise can induce the expression of TCAP and the transcriptional abundance increases with exercise intensity [29,33]. TCAP is mainly expressed in myocardial and skeletal muscle tissues [33,34]. This gene mutation can cause muscular dystrophy and hypertrophic or dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses using cDNA microarrays, RNA-seq, or qPCR are one way to obtain a deeper insight into the underlying biological processes and their genetic basis. By comparing gene expression in different states such as before and after specific exercises [16,17] and in different muscles [18,19], blood vs. muscle [20], or in various breeds [21,22] and hybrids [23], it may be possible to identify the genes involved in the biological context. Further investigations, in which analysis of eQTLs [24], noncoding RNAs [25,26], or changes in the methylation pattern [27][28][29] are in the foreground, deal with possible causes of expression changes, try to uncover alternative splice variants [17,18], selective isoform expression, or protein-/expression-changing SNPs in the genes involved [30][31][32], or focus on the combination of several omics levels [33][34][35] to better understand the relationships between genotype and phenotype as well as the influence of the environment.…”
Section: Introductionmentioning
confidence: 99%